Introduction: Religion on an Ordinary Day: An International Study of News Reporting - Poole, Elizabeth (Journal of religion, media and digital culture, 2021)
Abstract This article provides an introduction to an international study of religion on an ‘ordinary day’ in the news. Taking as its sample newspapers in the UK, Finland, Australia and Canada on 17 September in 2013, 2014 and 2015, the study aimed to provide a systematic analysis of ordinary or everyday coverage of religion in the news, providing an important contribution to research on religion in media, which tends to focus on specific events and controversies. Using both quantitative and qualitative methods to examine global, national and local stories about conventional, common religion and the secular sacred, the study also provides insights into conducting multi-national and interdisciplinary projects. While the findings demonstrate a fairly standardized representation of religion in mainstream news, with cultural Christianity dominating, the varying national and political contexts throw up some interesting specificities relating to increasing diversity and secularization experienced within wider processes of globalization.